2004
DOI: 10.1111/j.1368-5031.2004.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

FEV1 reversibility does not adequately predict effect of formoterol via Aerolizer® in chronic obstructive pulmonary disease

Abstract: Evaluation of patients with chronic obstructive pulmonary disease (COPD) often includes the use of post-bronchodilator reversibility testing to guide treatment decisions. Recommendations for reversibility testing differ and there is no universally accepted method or outcome criterion. A survey of recent clinical trials with beta2-agonists in COPD illustrates the diversity of methods used to assess reversibility and highlights the difficulty of comparing data from such trials. Two recent studies demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This supports previous assertions (reviewed by Mahler) 2 that a single reversibility test is not predictive of long-term outcomes with b 2 -agonists in patients with COPD; indicating that long-term treatment with formoterol may be equally effective in patients with low or high reversibility. Indeed, Muir et al 22 conclude that formoterol is effective in patients with COPD irrespective of their response to reversibility testing.…”
Section: Discussionmentioning
confidence: 99%
“…This supports previous assertions (reviewed by Mahler) 2 that a single reversibility test is not predictive of long-term outcomes with b 2 -agonists in patients with COPD; indicating that long-term treatment with formoterol may be equally effective in patients with low or high reversibility. Indeed, Muir et al 22 conclude that formoterol is effective in patients with COPD irrespective of their response to reversibility testing.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Of the 24 publications that met the inclusion criteria for this systematic review (see Table 1), 16 compared tiotropium with placebo, [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] seven compared tiotropium with an active comparator, [66][67][68][69][70][71][72] and one compared tiotropium with both placebo and an active comparator. 73 The QoL outcomes reported in the 24 included publications were mostly SGRQ and/or TDI (Tables 2 and 3).…”
Section: Summary Of Search Findingsmentioning
confidence: 99%
“…Similar results were obtained in a recent study in which little or no reversibility in bronchodilator testing was found not to be a good predictor of response to formoterol in COPD. (6) Therefore, COPD patients presenting a poor response to short-acting β 2 -agonists might present significant reversibility to formoterol, with considerable improvement in lung function and relief of symptoms. (4,6,24) Functional changes can be seen for weeks after the baseline testing and might be associated with several variables involved in the therapeutic efficacy of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…(6) Therefore, COPD patients presenting a poor response to short-acting β 2 -agonists might present significant reversibility to formoterol, with considerable improvement in lung function and relief of symptoms. (4,6,24) Functional changes can be seen for weeks after the baseline testing and might be associated with several variables involved in the therapeutic efficacy of the drug. (23,24) In a study involving 20 patients with partially reversible COPD and similar to the present study in design (formoterol and a placebo were compared), a significant response was observed even within 10 or 20 min after formoterol administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation